2018
DOI: 10.1039/c8ra05940c
|View full text |Cite
|
Sign up to set email alerts
|

Niobium phosphotungstates: excellent solid acid catalysts for the dehydration of fructose to 5-hydroxymethylfurfural under mild conditions

Abstract: A 5-HMF yield of 96.7% was obtained over an excellent heterogeneous catalyst NbPW-06 in DMSO at 80 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…The Sn loading decreased, i.e., Sn 3d 3/2 was decomposed into two peaks located at 493.38 and 495.98 eV, respectively, demonstrating the presence of a small amount of Sn (II) oxide in the sample. According to the literature for magnetite Qiu et al, 2018), the main peaks at 36.18 and 38.28 eV shown in the W 4f spectrum corresponded to W 4f 7/2 and W 4f 5/2 (Figure 3B). The binding energies of W 4f 7/2 and W 4f 5/2 in Sn 0.1 PW and Sn 0.75 PW showed a blueshift and slight decrease, respectively, and were weaker than that of pure HPW likely due to the interaction of the metal ion Sn n+ (n 2,4) with the anionic Keggin structural unit (Zhao et al, 2015).…”
Section: Catalyst Characterizationsupporting
confidence: 56%
“…The Sn loading decreased, i.e., Sn 3d 3/2 was decomposed into two peaks located at 493.38 and 495.98 eV, respectively, demonstrating the presence of a small amount of Sn (II) oxide in the sample. According to the literature for magnetite Qiu et al, 2018), the main peaks at 36.18 and 38.28 eV shown in the W 4f spectrum corresponded to W 4f 7/2 and W 4f 5/2 (Figure 3B). The binding energies of W 4f 7/2 and W 4f 5/2 in Sn 0.1 PW and Sn 0.75 PW showed a blueshift and slight decrease, respectively, and were weaker than that of pure HPW likely due to the interaction of the metal ion Sn n+ (n 2,4) with the anionic Keggin structural unit (Zhao et al, 2015).…”
Section: Catalyst Characterizationsupporting
confidence: 56%
“…Then, it can be noted that the system tested here with niobia treated at 100 • C for hour has one of the highest yields (13.7%) in a relatively short reaction time (two hours). Niobia-based catalysts [16,66,67] and supported WO 3 on zirconia [16,68] also demonstrated promising results. In a recent study, solid acid TiO 2 -SO 3 H showed a very high selectivity (71%) using low fructose concentration (0.1 mol L −1 ), 18 mg of catalyst at 140 • C for 1 h [26].…”
Section: Comparison With Other Catalysts For Aqueous Fructose Dehydra...mentioning
confidence: 96%
“…For the recycling of the catalyst, the humins were filtered out first, while the catalyst remained in the liquid phase and was recovered via liquid-liquid extraction (Figure 5 a). Hence, pseudo-liquid phase [47] (Table 2, entries 2-4), [41,48,49] of which Nb x H y PW [49] achieves the best catalytic results combining mild reaction conditions and good stability. For the hydrothermal synthesis of LA from different carbohydrate feedstocks (Table 2, entry 5), Kumar et al synthesized GaHPMo salts based on a sonochemical approach.…”
Section: Miscellaneous Saltsmentioning
confidence: 99%
“…Reproduced from Tao et al with permission from Elsevier [47]. (Table2, entries 2-4),[41,48,49] of which Nb x H y PW[49] achieves the best catalytic results combining mild reaction conditions and good stability. For the hydrothermal synthesis of LA from different carbohydrate feedstocks (Table2, entry 5), Kumar et al synthesized GaHPMo salts based on a sonochemical approach [50].…”
mentioning
confidence: 99%